Pemberdayaan Komunitas Wanita Tani pada Usaha Sayuran Organik di Wilayah Perkotaan - Aji Priambodo; Alda Laudya; Maman Sulaeman; Syaeful Bakhri (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
EMPOWERİNG WOMEN FARMERS' COMMUNİTİES İN ORGANİC VEGETABLE BUSİNESSES İN URBAN AREAS: The Women Farmers Group in Pekalipan Village, Pekalipan District, Cirebon City serves as a strategic platform for housewives to develop economic potential through utilizing yard land in RW.10. This empowerment program emerged as a solution for mothers who have been solely engaged in domestic routines without having other productive activities. Under the guidance of field extension officers from the Cirebon City Agriculture Department, these women farmers are encouraged to optimize their home yards by growing various types of organic vegetables. The applied concept pays careful attention to women's role balance, where gardening activities do not interfere with their primary responsibilities as mothers and wives, but instead provide real contributions to alleviating family economic burdens. Through intensive mentoring methods, this program aims to inspire enthusiasm and motivation among women farmers to improve family quality of life while building economic independence through environmentally friendly organic vegetable cultivation. This initiative demonstrates that women's empowerment can be achieved without abandoning their main responsibilities and roles within the family.